Mimicry of Stowe’s Uncle Tom’s Cabin and the formation of resistant slave narrative in Ishmael Reed’s Flight to Canada - Ramin, Zohreh; Roshnavand, Farshid Nowrouzi (Penerbit Universiti Kebangsaan Malaysia, 2017)
Postmodernism has as its major tenet the eradication of master-narratives in favor of marginalized voices. In so doing, it puts forward various strategies which, though different in methodology, are all critical of the dominant exclusionary discourses. Parodic mimicry is one of these subversive strategies which allows the anti-establishment artist to employ the discriminatory discursive practices and skillfully turn them on their heads. African American novelist Ishmael Reed adopts the postmodern technique of mimicry to severely criticize and disrupt the racist structure of the United States. In his “resistant” slave narrative Flight to Canada (1976), he takes to task the traditional historiography, showing how a so-called antislavery novel like Harriet Beecher Stowe’s Uncle Tom’s Cabin employs racial essentialism to reinforce the stereotypical representations of blacks and distort history to the benefit of white dominators. Through a parody of Stowe’s canonical work, Reed’s novel provides a space for the black consciousness to serve as an agentic subject and re-narrate the history of slavery, abolitionism and the Civil War. This paper aims to depict how Reed manages to rewrite the history of slavery in Flight to Canada by mimicking Stowe’s Uncle Tom’s Cabin.